Immunotropic Therapy of Arbovirus Infections in Children - O. G. Kimirilova; M. G. Romantsov; G. A. Kharchenko (Антибиотики и Химиотерапия)
Cytochemical indices of peripheral blood leukocytes were investigated. The results allowed to estimate the level of the disease severity and to control the immunotropic therapy efficacy. Dysbalance of the interleukocytic microbicidical systems (IMS) of neutrophils reflected the nonspecific resisistance and the state of the phagocytic system as an objective criterion of the adaptation syndrome. Association of the deficiency of the IMS components and blood serum fibronectin were considered as a predisposition of bacterial complications. Cycloferon activated the phagocyte metabolic activity and promoted elimination of the main clinical symptoms of the disease (acute infective damage of the meninges, temperature elevation, intoxication signs), thus making shorter the hospitalization terms.